A substrate film, a high temperature resistant swelling tape for lithium battery and a preparation method thereof

High-temperature resistant swelling tape is prepared by using a three-layer composite film composed of crosslinked thermoplastic polyurethane and multipolymer, which solves the problem of insufficient shrinkage deformation and thickness swelling performance in the prior art under high temperature conditions, and achieves efficient filling of the assembly gap of lithium batteries, enhancing the safety and life of the battery.

CN119189476BActive Publication Date: 2025-03-18ANHUI JUMEI BIOLOGICAL TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411306511.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-03-18
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

Existing swelling tape for lithium batteries is prone to shrink and deform under high temperature conditions, and the swelling performance in the thickness direction is insufficient, resulting in the inability to effectively fill the battery assembly gap, increasing the risk of battery short circuit and affecting battery life.

Method used

A three-layer composite film with cross-linked thermoplastic polyurethane as the intermediate layer, an ethylene-vinyl alcohol copolymer and an ethylene-acrylate-glycidyl acrylate copolymer as the outer layer, and a three-layer composite film with a polyethylene and an ethylene-acrylate-maleic anhydride copolymer as the inner layer as the base film, and a three-layer coextrusion blow molding mechanism was used to prepare a high-temperature resistant swelling tape.

Benefits of technology

The swelling tape does not shrink and deformation under high temperature conditions, and the swelling performance in the thickness direction is significantly improved. The swelling rate in 45℃ reaches more than 380%, and the swelling rate in 85℃ reaches more than 470%. It can effectively fill the assembly gap of lithium batteries and enhance the safety and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005049380610000111
    Figure BDA0005049380610000111
  • Figure BDA0005049380610000112
    Figure BDA0005049380610000112
  • Figure BDA0005049380610000121
    Figure BDA0005049380610000121
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to a substrate film, a high-temperature resistant swelling tape for lithium batteries, and a preparation method thereof. The substrate film is a three-layer composite film consisting of an outer layer, an intermediate layer, and an inner layer; a cross-linked unsaturated polyester polyol, a diisocyanate, and a chain extender are reacted and extruded through a twin-screw extruder to obtain an intermediate layer cross-linked thermoplastic polyurethane. The outer layer is composed of ethylene-vinyl alcohol copolymer and ethylene-acrylate-glycidyl acrylate copolymer; the inner layer is composed of polyethylene and ethylene-acrylate-maleic anhydride copolymer. The swelling tape prepared from the substrate film has a very high swelling ratio, is resistant to high temperatures, has good toughness, does not have the problem of high-temperature shrinkage and deformation, and after being soaked in an electrolyte, can effectively fill the gap between the lithium battery cell and the shell, avoid battery short circuit due to relative movement between the two, increase the safety of the battery, and has stable composition and high safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and specifically relates to a substrate film, a high temperature resistant swelling tape for lithium batteries and a preparation method thereof. Background Art

[0002] Today, the new energy industry is developing rapidly, which depends largely on the widespread promotion and application of new energy batteries. In the field of new energy vehicles, safety performance has always been the focus of consumers.

[0003] Among the many types of new energy batteries, cylindrical lithium batteries have the fastest development time, high degree of standardization, high yield rate, and the widest application. However, during the installation of cylindrical lithium batteries, in order to smoothly install the battery cells into the shell, a certain gap must be reserved between the battery cells and the shell. However, the existence of these expansion gaps has become a potential risk factor. During the use of the battery, especially after vibration or external impact, the assembly gap may cause the risk of battery short circuit due to the relative movement between the battery cell and the shell.

[0004] To solve this problem, the existing method is to wrap and bond a tape with a swelling function on the battery cell. When the battery cell wrapped with the swelling tape is assembled, there is still a certain gap, but when the tape contacts the electrolyte, it will swell and fill the entire gap, thereby fixing the battery cell and resisting external impact. This greatly improves the safety performance and service life of the battery.

[0005] The solutes in the electrolyte are generally lithium-containing materials such as lithium hexafluorophosphate. They are very afraid of water and will undergo violent decomposition reactions when in contact with water, thus affecting the efficacy and life of the battery. Therefore, the swelling tape is generally dried at about 110°C for 2 hours before use to avoid moisture from entering the battery as much as possible and causing adverse effects. Therefore, the swelling tape is required to be resistant to high temperatures.

[0006] CN111518481A discloses a special swelling tape for lithium batteries and its manufacturing process. The swelling tape includes a base layer and a coated pressure-sensitive adhesive layer. The base layer is composed of materials such as TPU, EVA, styrene resin solution and titanium dioxide. After the swelling tape contacts the electrolyte, it can only swell and deform in the length and width directions, but cannot swell in the thickness direction, which is not conducive to filling the gap. Moreover, the titanium dioxide may overflow from the tape after swelling and enter the electrolyte, which poses a risk of contaminating the electrolyte and affecting the battery performance.

[0007] CN 115717038A discloses a high temperature resistant swellable adhesive tape, comprising a base layer and a pressure sensitive adhesive layer, wherein the material used to form the base layer is thermoplastic polyurethane with a Shore hardness of not less than 70D. However, after contacting the electrolyte, the swellable adhesive tape can only swell and deform in the length and width directions, but cannot swell in the thickness direction, which is not conducive to filling the gap, and the swelling and deformation in the length and width directions may cause deformation of the battery, thereby affecting the battery life.

[0008] CN 114213983 A discloses a base film of a swelling tape for lithium batteries and a swelling tape for lithium batteries, which can swell at a high rate in the area direction, have a high swelling rate in the length and width directions, and have average swelling performance in the thickness direction. Swelling deformation in the length and width directions may cause deformation of the battery, thereby affecting the battery life.

[0009] CN111995957A discloses a directional polystyrene swelling tape with a high expansion ratio and a preparation method thereof. The swelling tape is composed of a single-sided release directional polystyrene film substrate and an acrylate adhesive layer. Although the swelling ratio is high, the swelling of the tape is mainly achieved by the microscopic holes generated by directional stretching to adsorb electrolyte solvents. The directional stretched film is prone to shrinkage in the width direction at high temperatures, thereby affecting the assembly gap and easily causing battery deformation. In addition, the tape has low temperature resistance and is not resistant to high temperatures. After drying, it shrinks at high temperatures and cannot be used.

[0010] CN115058014A discloses a polyether-hydrogenated polybutadiene diol and its preparation method, thermoplastic polyurethane, and lithium battery swelling tape. The swelling rate in the electrolyte is too low, only 44.1-54.6%, and there is no indication whether it is swelling in the length, width or thickness direction.

[0011] It can be seen that the existing swelling tape has a low expansion ratio, especially it cannot swell in the thickness direction or the swelling ratio in the thickness direction is low, which is not conducive to filling the gap. It has a large swelling deformation in the length and width direction, which can easily cause battery deformation, affect battery life, high temperature dissolution, high temperature shrinkage deformation and other problems.

[0012] The swelling tape mainly consists of two parts: substrate film and adhesive. The swelling is contributed by the substrate film, so the swelling ratio, whether it dissolves at high temperature, whether it expands in the thickness direction, whether it shrinks and deforms, etc. are all closely related to the substrate film. Therefore, how to design and manufacture a substrate film and swelling tape that can withstand high temperatures, does not have the problem of high-temperature shrinkage and deformation, does not have obvious shrinkage and deformation in the length and width directions after being soaked in electrolyte, has good swelling performance in the thickness direction, has stable composition, and has high safety performance is of great significance. Summary of the invention

[0013] The purpose of the present invention is to provide a substrate film for a high-temperature resistant swelling tape. The swelling tape prepared from the substrate film has a very high swelling ratio, can withstand high temperatures, has good toughness, and does not have the problem of high-temperature shrinkage and deformation. After being soaked in electrolyte, it can effectively fill the gap between the lithium battery cell and the shell to avoid battery short circuit due to relative movement between the two, thereby increasing the safety of the battery, and has stable composition and high safety performance. The present invention also provides a swelling tape for lithium batteries prepared thereby and a preparation method thereof.

[0014] The invention provides a high temperature resistant swelling tape substrate film for lithium batteries, wherein the substrate film is a three-layer composite film consisting of an outer layer, an intermediate layer and an inner layer; the intermediate layer is a cross-linked thermoplastic polyurethane; the preparation method of the cross-linked thermoplastic polyurethane is as follows: cross-linked unsaturated polyester polyol, diisocyanate and a chain extender are reacted and extruded through a twin-screw extruder to obtain the cross-linked thermoplastic polyurethane.

[0015] Preferably, the cross-linked unsaturated polyester polyol is obtained by reacting a polyol and a polyacid in a molar ratio of 1:1.05-1.1; the polyacid is a mixture of succinic acid and fumaric acid in a molar ratio of 99.0-99.9:0.1-1; the polyol is a mixture of 1,4-butanediol and glycerol in a molar ratio of 99.0-99.9:0.1-1.

[0016] Preferably, the cross-linked thermoplastic polyurethane has a weight average molecular weight of 100,000 to 400,000 and a gel fraction of 0.1 to 2.0 wt%.

[0017] Preferably, the mass ratio of the cross-linked unsaturated polyester polyol, diisocyanate and chain extender is 50-55:40-41:8.

[0018] Preferably, the chain extender is ethylene glycol and dibenzoyl peroxide; dibenzoyl peroxide accounts for 0.01-0.05wt% of the chain extender. The diisocyanate is preferably one or more of diphenylmethane diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, naphthalene diisocyanate, toluene diisocyanate or p-phenylene diisocyanate.

[0019] Preferably, the outer layer is composed of 70-90 wt% of ethylene-vinyl alcohol copolymer and 10-30 wt% of ethylene-glycidyl acrylate copolymer or ethylene-acrylate-glycidyl acrylate copolymer;

[0020] The inner layer is composed of 30-50 wt% of polyethylene and 50-70 wt% of ethylene-acrylate-maleic anhydride copolymer.

[0021] Preferably, the ethylene content in the ethylene-vinyl alcohol copolymer (EVOH) is 29 to 44 mol%. The inventors have found that if the ethylene content is too low, the melting point of EVOH is too high, which makes the processing temperature too high; if the ethylene content is too high, the strength and barrier properties of EVOH will be too low, which will affect the strength of the substrate film.

[0022] Preferably, the content of glycidyl acrylate in the ethylene-glycidyl acrylate copolymer is 6 to 19 wt %.

[0023] More preferably, the outer layer is composed of 70-90wt% of ethylene-vinyl alcohol copolymer and 10-30wt% of ethylene-acrylate-glycidyl acrylate copolymer; the content of acrylate in the ethylene-acrylate-glycidyl acrylate copolymer is 15-27wt%, and the content of glycidyl acrylate is 6-19wt%. By adding the copolymer containing acrylate, the toughness of the product can be improved.

[0024] Preferably, the polyethylene is metallocene polyethylene with a melt index of 1 to 1.8 g / 10 min;

[0025] The content of acrylate in the ethylene-acrylate-maleic anhydride copolymer is 6-29 wt %, and the content of maleic anhydride is 1.3-3.6 wt %.

[0026] Preferably, the thickness ratio of the outer layer, the middle layer and the inner layer of the three-layer composite film is 1-1.5:4:1.5-2.

[0027] As we all know, the function of the swelling tape is to wrap around the battery cell of the lithium battery. After being soaked in electrolyte, it fills the assembly gap between the battery cell and the shell through the expansion function generated by swelling. Therefore, only swelling in the thickness direction is really needed for battery assembly; while swelling in the length and width directions may cause deformation of the battery, thereby affecting the battery life.

[0028] The electrolyte of lithium battery is mainly composed of electrolyte solvent and solute. The electrolyte solvent mainly includes ethylene carbonate, propylene carbonate, diethyl carbonate, etc., and the solute mainly includes lithium hexafluorophosphate, etc. There are a large number of urethane bonds on the molecular chain of polyurethane (TPU), which has a large polarity and is close to the solubility parameter and polarity of the electrolyte solvent. The two are easy to dissolve or swell together.

[0029] Therefore, in view of the problems existing in the prior art, the present invention uses the following technical means to achieve the above-mentioned purpose:

[0030] First, cross-linked thermoplastic polyurethane is used to replace the existing polyurethane. In the process of producing polyester polyol, fumaric acid and glycerol are added to introduce unsaturated double bonds and branched structures into the molecular chain of polyester polyol, thereby obtaining cross-linked unsaturated polyester polyol. In the process of producing polyurethane resin, due to the trifunctional group of glycerol, a branched structure has been introduced into the molecular chain of polyester polyol. After adding diisocyanate (preferably diphenylmethane diisocyanate, MDI) and chain extender diol (ethylene glycol, EG), a network cross-linked structure will be formed; in addition, after adding benzoyl peroxide (BPO), the double bonds on the polyester polyol are opened, thereby introducing a carbon-carbon branched network structure into the molecular chain, that is, fumaric acid and glycerol enable the molecular chain of cross-linked thermoplastic polyurethane to obtain a double cross-linked network structure. A cross-linked network structure is introduced into the polyurethane molecular chain. The cross-linking points are all stable carbon-carbon bonds, which not only reduces the risk of electrolyte dissolution; at the same time, the cross-linked network structure will produce more gaps at the microscopic level than the linear structure, so that the material can absorb more electrolyte and produce a greater swelling effect.

[0031] Preferably, the cross-linked unsaturated polyester polyol is obtained by reacting a polyol and a polyacid at a molar ratio of 1:1.05-1.1; wherein the polyacid is a mixture of succinic acid and fumaric acid at a molar ratio of 99.0-99.9:0.1-1; and the polyol is a mixture of 1,4-butanediol and glycerol at a molar ratio of 99.0-99.9:0.1-1. The addition amount of unsaturated dibasic acid and triol should not be too high, otherwise gel will appear, resulting in crystal points on the film, and excessive cross-linking may even make the polyurethane a thermosetting material.

[0032] Second, the substrate film is made into a three-layer composite structure, the middle layer is a cross-linked thermoplastic polyurethane, which mainly plays a swelling function, and the outer layer and inner layer are protective layers. The outer layer and inner layer are both materials with good film-forming properties. They mainly protect the middle layer, and at the same time can further limit the expansion of the substrate film in the length and width directions, improve battery life, and reduce the risk of dissolution of the substrate film, because the swelling rate will drop a lot after dissolution, thereby playing a role in increasing the swelling rate. The outer layer material EVOH has a relatively high mechanical strength due to the intramolecular hydrogen bonding, and the polyethylene in the inner layer material has good toughness. The outer layer provides rigidity and mechanical strength for the substrate film, the inner layer provides flexibility and adhesion for the substrate film, and the middle layer provides swelling.

[0033] The outer layer material is selected from ethylene-vinyl alcohol copolymer (EVOH) and ethylene-glycidyl acrylate copolymer or ethylene-acrylate-glycidyl acrylate copolymer (EMG), and EVOH and EMG are more preferred. EVOH has good film-forming properties and a large number of hydroxyl groups on the molecular chain. It can form strong hydrogen bonds with the amino ester group, terminal hydroxyl group and carboxyl group on the TPU molecular chain. At the same time, there are a large number of acrylate groups and epoxy groups on the EMG molecular chain. The acrylate group has good compatibility with TPU, and the epoxy group can react with the terminal carboxyl group on TPU, further increasing the compatibility with TPU. Therefore, the compatibility and affinity between the outer layer and the middle layer are good, avoiding stratification. Since there are a large number of polar group hydroxyl groups on the EVOH molecular chain and a large number of polar group epoxy groups and acrylate groups on the side chain of EMG, their polarity is close to that of the electrolyte, which is conducive to the penetration of the electrolyte into the middle layer.

[0034] At the same time, the presence of trace amounts of water in the electrolyte may generate a strong acidic substance, which will cause the swelling tape to dissolve. EVOH has a good barrier effect on moisture. Therefore, choosing EVOH as the outer layer material will also provide a certain degree of protection for the middle layer.

[0035] More preferably, the outer layer is composed of 70-90wt% of ethylene-vinyl alcohol copolymer and 10-30wt% of ethylene-acrylate-glycidyl acrylate copolymer; the content of acrylate in the ethylene-acrylate-glycidyl acrylate copolymer is 15-27wt%, and the content of glycidyl acrylate is 6-19wt%. The presence of acrylate will improve the toughness of the copolymer. At the same time, there are a large number of acrylate groups and epoxy groups on acrylate and glycidyl acrylate. The acrylate group has excellent compatibility with the amino ester group, hydroxyl group and carboxyl group on the TPU molecular chain. The most important thing is that the epoxy group can also react with the carboxyl group on TPU, which further enhances the compatibility between EVOH and TPU.

[0036] The inner layer materials are polyethylene (PE) and ethylene-acrylate-maleic anhydride copolymer (EMH). PE has excellent film-forming properties and shares a common polymer segment -CH2-CH2- with EMH, so the two have good compatibility. There are a large number of acrylate groups and maleic anhydride groups on the EMH molecular chain. Maleic anhydride can react with the hydroxyl and amino groups on TPU, and acrylate can also form strong hydrogen bonds with the hydroxyl and amino groups on TPU. Therefore, EMH can greatly improve the compatibility between PE and TPU, and can effectively avoid stratification of the inner and middle layers.

[0037] Since adhesives are mainly acrylate products, the inner layer of the substrate film needs to be coated with adhesive to make a tape, so the inner layer of the substrate film also needs to have good adhesion with the adhesive. Our inner layer material just happens to have EMH added. There are a large number of maleic anhydride groups and acrylate groups on the EMH molecular chain, which have good affinity with acrylate adhesives.

[0038] The present invention also provides a high temperature resistant swelling tape for lithium batteries, which is formed by compounding the outer layer of the substrate film for the high temperature resistant swelling tape with an adhesive.

[0039] The present invention also provides a method for preparing a high temperature resistant swelling tape for a lithium battery, comprising the following steps:

[0040] (1) Outer layer material: Weigh ethylene-vinyl alcohol copolymer, ethylene-glycidyl acrylate copolymer or ethylene-acrylate-glycidyl acrylate copolymer, and stir to mix well;

[0041] (2) Inner layer material: Weigh polyethylene and ethylene-acrylate-maleic anhydride copolymer, and stir to mix evenly;

[0042] (3) Middle layer material:

[0043] S1: Mix succinic acid and fumaric acid for later use;

[0044] S2: Mix 1,4-butanediol and glycerol for later use;

[0045] S3: adding the mixture of succinic acid and fumaric acid obtained in step S1 and the mixture of 1,4-butanediol and glycerol obtained in step S2 into a reaction container for reaction to obtain the cross-linked unsaturated polyester polyol;

[0046] S4: mixing dibenzoyl peroxide and ethylene glycol to obtain a chain extender for later use;

[0047] S5: mixing the cross-linked unsaturated polyester polyol obtained in step S3, the chain extender obtained in step S4, and the catalyst, then adding diisocyanate, adding the mixture to a twin-screw extruder through a feeding and perfusion system, performing reaction extrusion, pelletizing, and drying to obtain a cross-linked thermoplastic polyurethane, which is the intermediate layer material;

[0048] (4) respectively adding the outer layer material, the middle layer material and the inner layer material into corresponding extruders, and obtaining a three-layer composite film by three-layer co-extrusion blow molding or casting, namely, the substrate film;

[0049] (5) An adhesive is applied on the inner layer material side of the substrate film to obtain the high temperature resistant swelling tape.

[0050] Preferably, in step (4), the temperature of each zone of the outer layer machine corresponding to the outer layer material is 150-180°C, the temperature of each zone of the middle layer machine corresponding to the middle layer material is 140-180°C, the temperature of each zone of the inner layer machine corresponding to the inner layer material is 140-180°C, the temperature of the connecting head of the extruder is 180±10°C, and the temperature of the die head is 170±10°C.

[0051] The present invention utilizes a three-layer co-extrusion blow molding machine to obtain a substrate film by blow molding or casting. The three-layer co-extrusion blow molding machine has three independent single-screw extruders. The outer layer material, the middle layer material and the inner layer material are respectively added to the corresponding extruders, and then blown into a film under heating. The thickness of the three layers is controlled by controlling the feeding amount, and finally a substrate film with a three-layer composite structure is obtained.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] (1) The substrate film and swelling tape prepared by the present invention are resistant to high temperatures, and will not show obvious shrinkage deformation in the length and width directions under high temperature conditions, and have stable high temperature performance.

[0054] (2) The swelling tape prepared by the present invention does not show obvious shrinkage deformation in the length and width directions after being soaked in electrolyte, and has good swelling performance in the thickness direction. The swelling rate at 45°C is above 380%, and the swelling rate at 85°C is above 470%. After swelling, it can fully fill the assembly gap of the lithium-ion battery without causing deformation of the battery, and the battery life is long.

[0055] (3) The components of the present invention are stable, there is no problem of electrolyte contamination due to overflow from the tape, and the safety performance is high. DETAILED DESCRIPTION

[0056] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0057] The main sources of raw materials are as follows:

[0058] Bismuth neodecanoate was from Jiangsu Evergreen New Materials Technology Co., Ltd.;

[0059] Fumaric acid was from Anhui Xuelang Biotechnology Co., Ltd.;

[0060] Diphenylmethane diisocyanate comes from Wanhua Chemical Group.

[0061] The equipment parameters of the three-layer co-extrusion film blowing machine used in the specific embodiment of the present invention are: the screw diameter of the outer layer extruder is 45mm, the length-diameter ratio is 28:1; the screw diameter of the middle layer extruder is 55mm, the length-diameter ratio is 28:1; the screw diameter of the outer layer extruder is 45mm, the length-diameter ratio is 28:1, the die head diameter is 400mm, and the die gap is 2mm.

[0062] Example 1

[0063] A method for preparing a high temperature resistant swelling tape for a lithium battery comprises the following steps:

[0064] (1) Outer layer material: weigh 90 kg of ethylene-vinyl alcohol copolymer (SoarnoL TM A4412B, ethylene content 44 mol%) and 10 kg ethylene-acrylate-glycidyl acrylate copolymer (LOTADE TM AX8900, methyl acrylate content 24wt%, glycidyl acrylate content 8wt%), mixed evenly by a stirrer and set aside.

[0065] (2) Inner layer material: weigh 30 kg of metallocene polyethylene (Exceed TM 1018CA, melt index 1.0g / 10min) and 70kg ethylene-acrylate-maleic anhydride copolymer (LOTADER TM 4210, butyl acrylate content 6.5wt%, maleic anhydride content 3.6wt%), mixed evenly in a stirrer and set aside.

[0066] (3) The preparation steps of the intermediate layer material (cross-linked thermoplastic polyurethane TPU-1) are as follows:

[0067] S1: Succinic acid and fumaric acid are mixed in a molar ratio of 99.5:0.5 for later use;

[0068] S2: Mix 1,4-butanediol (BDO) and glycerol in a molar ratio of 99.0:1.0 for later use;

[0069] S3: adding the mixture of succinic acid and fumaric acid obtained in step S1 and the mixture of 1,4-butanediol (BDO) and glycerol obtained in step S2 into a reaction container at a molar ratio of 1:1.1, reacting at 190° C. for 10 h, and then continuing to react at 210° C. and -0.1 MPa for 4 h to obtain a cross-linked unsaturated polyester polyol with a number average molecular weight of 1500;

[0070] S4: mixing dibenzoyl peroxide and ethylene glycol to obtain a chain extender for standby use, wherein the dibenzoyl peroxide accounts for 0.01 wt % of the chain extender;

[0071] S5: 52kg of the cross-linked unsaturated polyester polyol obtained in step S3, 8kg of the chain extender obtained in step S4, and 0.01kg of bismuth neodecanoate catalyst were mixed, stirred at 50°C for 4 hours to obtain the configured polyester polyol, and then the configured polyester polyol and 40kg of diphenylmethane diisocyanate (MDI-100) were added to the twin-screw extruder through the feeding and perfusion system, and the reaction extrusion was carried out at 190°C (main engine speed 200r / min), pelletized, and dried to obtain polyurethane TPU-1. The weight average molecular weight is 262,000, and the gel fraction is 1.32wt%.

[0072] (4) adding the outer layer material, the middle layer material and the inner layer material to the corresponding extruders respectively, the temperature of each zone of the outer layer machine is 150-160-170-180°C, the temperature of each zone of the middle layer machine is 140-160-170-180°C, the temperature of each zone of the inner layer machine is 140-160-170-180°C, the temperature of the connector is 190°C, the temperature of the die head is 175°C, and a three-layer composite film is obtained by a three-layer co-extrusion film blowing machine in a three-layer co-extrusion blow molding or cast film manner, wherein the thickness ratio of the three-layer film is outer layer: middle layer: inner layer = 1:4:2, and the film is rolled up after blowing, the blowing ratio is 2.2, and the film thickness is 0.051 mm, to obtain a substrate film;

[0073] (5) Applying an adhesive on one side of the inner layer material of the substrate film to obtain a high temperature resistant swelling tape for lithium batteries; the adhesive is a conventional commercial product in the art.

[0074] The substrate film obtained in step (4) was cut into 30*20 mm for testing.

[0075] Example 2

[0076] A method for preparing a high temperature resistant swelling tape for a lithium battery comprises the following steps:

[0077] (1) Outer layer material: weigh 80 kg of ethylene-vinyl alcohol copolymer (SoarnoL TM E3808, ethylene content 38 mol%) and 20 kg ethylene-acrylate-glycidyl acrylate copolymer (LOTADE TM AX8700, butyl acrylate content 25wt%, GMA content 8wt%), mixed evenly by a stirrer and set aside.

[0078] (2) Inner layer material: weigh 40 kg of metallocene polyethylene (ELITE TM 5400G, melt index 1.0g / 10min) and 60kg ethylene-acrylate-maleic anhydride copolymer (LOTADER TM 3430, methyl acrylate content 15wt%, maleic anhydride content 3.1wt%), mixed evenly by a stirrer and set aside.

[0079] (3) Intermediate layer material (cross-linked thermoplastic polyurethane TPU-2): The preparation method is the same as that of TPU-1 prepared in Example 1, but the raw materials are different: the molar ratio of succinic acid to fumaric acid is 99.0:1.0, the molar ratio of BDO to glycerol is 99.5:0.5, and dibenzoyl peroxide accounts for 0.03wt% of the chain extender. The weight average molecular weight of the obtained TPU-2 is 245,000, and the gel fraction is 1.45wt%.

[0080] (4) adding the outer layer material, the middle layer material and the inner layer material to the corresponding extruders respectively, the temperature of each zone of the outer layer machine is 150-165-175-185°C, the temperature of each zone of the middle layer machine is 140-165-175-185°C, the temperature of each zone of the inner layer machine is 140-155-175-180°C, the temperature of the connector is 190°C, the temperature of the die head is 180°C, and a three-layer composite film is obtained by a three-layer co-extrusion film blowing machine in a three-layer co-extrusion blow molding or cast film manner, wherein the thickness ratio of the three-layer film is outer layer: middle layer: inner layer = 1:4:2, and the film is rolled up after blowing, the blowing ratio is 2.3, and the film thickness is 0.050 mm, to obtain a substrate film;

[0081] (5) Applying an adhesive on one side of the inner layer material of the substrate film to obtain a high temperature resistant swelling tape for lithium batteries; the adhesive is a conventional commercial product in the art.

[0082] The substrate film obtained in step (4) was cut into 30*20 mm for testing.

[0083] Example 3

[0084] A method for preparing a high temperature resistant swelling tape for a lithium battery comprises the following steps:

[0085] (1) Outer layer material: weigh 70 kg of ethylene-vinyl alcohol copolymer (EVASIN TM EV 2951F, ethylene content 29 mol%) and 30 kg ethylene-glycidyl acrylate copolymer (IGETBOND TM BF-E, glycidyl acrylate content 19wt%), mixed evenly with a stirrer and set aside.

[0086] (2) Inner layer material: weigh 50 kg of metallocene polyethylene (ELITE TM 5220G, melt index 1.8g / 10min) and 50kg ethylene-acrylate-maleic anhydride copolymer (LOTADER TM 3410, butyl acrylate content 17wt%, maleic anhydride content 3.1wt%), mixed evenly by a stirrer and set aside.

[0087] (3) Intermediate layer material (cross-linked thermoplastic polyurethane TPU-3): The preparation method is the same as that of TPU-1 prepared in Example 1, but the raw materials are different: the molar ratio of succinic acid to fumaric acid is 99.3:0.7, the molar ratio of BDO to glycerol is 99.4:0.6, and dibenzoyl peroxide accounts for 0.03wt% of the chain extender. The weight average molecular weight of the obtained TPU-3 is 228,000, and the gel fraction is 1.06wt%.

[0088] (4) adding the outer layer material, the middle layer material and the inner layer material to the corresponding extruders respectively, the temperature of each zone of the outer layer machine is 150-160-170-180°C, the temperature of each zone of the middle layer machine is 140-160-170-175°C, the temperature of each zone of the inner layer machine is 140-160-165-170°C, the temperature of the connector is 185°C, the temperature of the die head is 170°C, and a three-layer composite film is obtained by a three-layer co-extrusion film blowing machine in a three-layer co-extrusion blow molding or cast film manner, wherein the thickness ratio of the three-layer film is outer layer: middle layer: inner layer = 1:4:1.5, and the film is rolled up after blowing, the blowing ratio is 2.25, and the film thickness is 0.052 mm, to obtain a substrate film;

[0089] (5) Applying an adhesive on one side of the inner layer material of the substrate film to obtain a high temperature resistant swelling tape for lithium batteries; the adhesive is a conventional commercial product in the art.

[0090] The substrate film obtained in step (4) was cut into 30*20 mm for testing.

[0091] Example 4

[0092] A method for preparing a high temperature resistant swelling tape for a lithium battery comprises the following steps:

[0093] (1) Outer layer material: weigh 75 kg of ethylene-vinyl alcohol copolymer (EVASIN TM EV 3251FT, ethylene content 32 mol%) and 25 kg ethylene-acrylate-glycidyl acrylate copolymer (IGETBOND TM BF-7M, methyl acrylate content 27wt%, glycidyl acrylate content 6wt%), mixed evenly by a stirrer and set aside.

[0094] (2) Inner layer material: weigh 45 kg of metallocene polyethylene (Daelimpoly TM XP5300, melt index 1.5g / 10min) and 55kg ethylene-acrylate-maleic anhydride copolymer (LOTADER TM 4700, ethyl acrylate content 29wt%, maleic anhydride content 1.3wt%), mixed evenly in a stirrer and set aside.

[0095] (3) Intermediate layer material (cross-linked thermoplastic polyurethane TPU-4): The preparation method is the same as that of TPU-1 prepared in Example 1, but the raw materials are different: the molar ratio of succinic acid to fumaric acid is 99.7:0.3, the molar ratio of BDO to glycerol is 99.6:0.4, and the molar ratio of dibenzoyl peroxide to ethylene glycol is 0.02:100. The weight average molecular weight of the obtained TPU-4 is 209,000, and the gel fraction is 0.85wt%.

[0096] (4) adding the outer layer material, the middle layer material and the inner layer material to the corresponding extruders respectively, the temperature of each zone of the outer layer machine is 150-160-170-180°C, the temperature of each zone of the middle layer machine is 140-160-170-175°C, the temperature of each zone of the inner layer machine is 140-160-165-180°C, the temperature of the connector is 185°C, the temperature of the die head is 175°C, and a three-layer composite film is obtained by a three-layer co-extrusion film blowing machine in a three-layer co-extrusion blow molding or cast film manner, wherein the thickness ratio of the three-layer film is outer layer: middle layer: inner layer = 1.5:4:1.5, and the film is rolled up after blowing, the blowing ratio is 2.2, and the film thickness is 0.051 mm, to obtain a substrate film;

[0097] (5) Applying an adhesive on one side of the inner layer material of the substrate film to obtain a high temperature resistant swelling tape for lithium batteries; the adhesive is a conventional commercial product in the art.

[0098] The substrate film obtained in step (4) was cut into 30*20 mm for testing.

[0099] Comparative Example 1

[0100] A high temperature swelling resistant tape for lithium batteries is basically the same as Example 2, the only difference being that TPU-CK is used to replace the intermediate layer material TPU-2 of Example 2.

[0101] Among them, the specific preparation method of TPU-CK is as follows:

[0102] S1: Succinic acid and 1,4-butanediol (BDO) were added into a reaction vessel at a molar ratio of 1:1.1, reacted at 190°C for 10 hours, and then continued to react at 210°C and -0.1 MPa for about 4 hours to obtain polybutylene succinate diol with a number average molecular weight of 1500.

[0103] S2: 52 parts of polybutylene succinate diol prepared in step S1, 8 parts of ethylene glycol (EG) and 0.01 parts of bismuth neodecanoate catalyst are mixed, and stirred at 50°C for 4 hours to obtain a prepared polyester polyol, and then the prepared polyester polyol and 40 parts of diphenylmethane diisocyanate (MDI-100) are added into a twin-screw extruder through a feeding and perfusion system, and reaction extrusion is carried out at 190°C (main engine speed is 200r / min), pelletized, and dried to obtain polyurethane TPU-CK with a weight average molecular weight of 236,000 and a gel fraction of 0.18wt%.

[0104] Comparative Example 2

[0105] A high temperature resistant swelling tape for lithium batteries is basically the same as Example 2, the only difference being that the outer layer, the middle layer, and the inner layer materials are all replaced with TPU-2, and the rest is the same as Example 2.

[0106] Comparative Example 3

[0107] A high temperature resistant swelling tape for lithium battery, which is basically the same as Example 2, except that the ethylene-vinyl alcohol copolymer in the outer layer material is replaced by polystyrene (STYROLUTION TM PS1540).

[0108] Comparative Example 4

[0109] It is basically the same as Example 2, the only difference being that the molar ratio of the intermediate layer material: succinic acid to fumaric acid is 98:2, and the gel fraction of the obtained TPU is 3.04 wt%.

[0110] Comparative Example 5

[0111] It is basically the same as Example 2, the only difference being that the molar ratio of the intermediate layer material: BDO to glycerol is 97.5:2.5, and the gel fraction of the obtained TPU is 5.16 wt %.

[0112] In the blown film production process of Comparative Examples 4 and 5, there were too many crystal points, and holes frequently appeared in the film, so that normal production could not be performed and normal films could not be obtained. This was because the addition amount of unsaturated dibasic acid fumaric acid and triol glycerol was too large, resulting in too high a gel fraction.

[0113] The substrate films prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were cut into pieces of about 30*20 mm, and the following tests were performed respectively:

[0114] Swelling rate test method: The ratio of the size of the film after immersion in electrolyte to the size before immersion is the swelling rate or expansion rate.

[0115] Among them, the lithium battery electrolyte comes from Guangzhou Tianci High-tech Materials Co., Ltd. The electrolyte solvent composition is: ethylene carbonate: propylene carbonate: diethyl carbonate = 1:1:1 (volume ratio), and the solute is lithium hexafluorophosphate.

[0116] Shrinkage test conditions: 110℃, drying for 2h. Shrinkage calculation method: The difference between the length or width of the film after drying and the length or width before drying, and the ratio of the length or width before drying is the shrinkage.

[0117] The test results are shown in Table 1 and Table 2.

[0118] Table 1

[0119]

[0120] Table 2

[0121]

[0122]

[0123] By comparing the data in Table 1 and Table 2, it can be seen that the substrate films prepared in Examples 1 to 4 did not show obvious shrinkage deformation in the length and width directions after drying at 110°C; Comparative Example 1 had a relatively small shrinkage deformation due to the protection of the protective layer; Comparative Example 2 had no protection of the outer and inner protective layers, and had a certain shrinkage, but due to the cross-linking, the shrinkage was not particularly large; Comparative Example 3 had a PS material as the outer layer material, which was an amorphous material. Microscopically, the molecular chain existed in the form of a random coil, and the glass transition temperature was 105°C. When dried and heated at 110°C, the molecular chain movement was relatively active, and a large shrinkage deformation occurred. The thickness of Examples 1 to 4 and Comparative Examples 1 to 3 before and after drying was 0.052±0.002mm, and there was no obvious change in thickness before and after drying. This shows that the swelling tape of the present invention can withstand high temperatures.

[0124] At the same time, it can be seen from the data in Tables 1 and 2 that after the substrate films prepared in Examples 1 to 4 are soaked in the electrolyte, the swelling rate in the length and width directions is not very large, and the swelling rate in the thickness direction is relatively high. The swelling rate at 45°C is above 380%, and the swelling rate at 85°C reaches above 470%. After swelling, they can fully fill the assembly gap. In Comparative Example 1, the cross-linked TPU is replaced with uncross-linked TPU, and the swelling rate at either 45°C or 85°C is obviously lower than that of the cross-linked TPU of the present invention; in Comparative Example 2, after both the outer layer and the inner layer are replaced with cross-linked TPU, it is equivalent to that the three-layer structure becomes a one-layer structure, without the protection of the inner and outer layers, the swelling rate at 45°C does not increase, but decreases, which means that without the protection of the outer layer, partial dissolution occurs, but the lack of dissolution is not apparent. However, obvious dissolution occurs at 85°C, and the dissolved part will not swell again, and the swelling will naturally decrease a lot; in Comparative Example 3, the outer layer is replaced with PS material. Since the polarity of PS material is weak and its compatibility with the electrolyte is poor, it is difficult for the electrolyte to penetrate PS, so the swelling rate is not too high whether it is immersed at 45°C or 85°C.

Claims

1. A high temperature resistant swelling tape substrate film for lithium battery, characterized in that: The substrate film is a three-layer composite film consisting of an outer layer, an intermediate layer and an inner layer; the intermediate layer is a cross-linked thermoplastic polyurethane; the preparation method of the cross-linked thermoplastic polyurethane is: cross-linked unsaturated polyester polyol, diisocyanate and chain extender are reacted and extruded through a twin-screw extruder to obtain the cross-linked thermoplastic polyurethane; The cross-linked unsaturated polyester polyol is obtained by reacting a polyol and a polyacid in a molar ratio of 1:1.05-1.1; The polyacid is a mixture of succinic acid and fumaric acid in a molar ratio of 99.0-99.9:0.1-1; The polyol is a mixture of 1,4-butanediol and glycerol in a molar ratio of 99.0-99.9:0.1-1; The outer layer is composed of 70-90 wt % of ethylene-vinyl alcohol copolymer and 10-30 wt % of ethylene-glycidyl acrylate copolymer or ethylene-acrylate-glycidyl acrylate copolymer; The inner layer is composed of 30-50 wt % of polyethylene and 50-70 wt % of ethylene-acrylate-maleic anhydride copolymer.

2. The high temperature resistant swelling tape substrate film for lithium battery according to claim 1, characterized in that: The cross-linked thermoplastic polyurethane has a weight average molecular weight of 100,000 to 400,000 and a gel fraction of 0.1 to 2.0 wt %; The mass ratio of the cross-linked unsaturated polyester polyol, diisocyanate and chain extender is 50-55:40-41:8; the chain extender is ethylene glycol and dibenzoyl peroxide; and the dibenzoyl peroxide accounts for 0.01-0.05wt% of the chain extender.

3. The high temperature resistant swelling tape substrate film for lithium battery according to claim 1, characterized in that: The outer layer is composed of 70-90wt% of ethylene-vinyl alcohol copolymer and 10-30wt% of ethylene-acrylate-glycidyl acrylate copolymer; the content of acrylate in the ethylene-acrylate-glycidyl acrylate copolymer is 15-27wt%, and the content of glycidyl acrylate is 6-19wt%.

4. The high temperature resistant swelling tape substrate film for lithium battery according to claim 1, characterized in that: The ethylene content of the ethylene-vinyl alcohol copolymer is 29-44 mol%; The polyethylene is metallocene polyethylene with a melt index of 1-1.8 g / 10 min; The content of acrylate in the ethylene-acrylate-maleic anhydride copolymer is 6-29 wt %, and the content of maleic anhydride is 1.3-3.6 wt %.

5. The high temperature resistant swelling tape substrate film for lithium battery according to claim 1, characterized in that: The thickness ratio of the outer layer, the middle layer and the inner layer of the three-layer composite film is 1-1.5:4:1.5-2.

6. A high temperature swelling tape for lithium batteries, characterized in that: The high temperature resistant swelling tape is obtained by compounding the inner layer of the substrate film according to any one of claims 1 to 5 with an adhesive.

7. A method for preparing the high temperature resistant swelling tape for lithium battery according to claim 6, characterized in that: The following steps are involved: (1) Outer layer material: Weigh ethylene-vinyl alcohol copolymer, ethylene-glycidyl acrylate copolymer or ethylene-acrylate-glycidyl acrylate copolymer, and stir to mix evenly; (2) Inner layer material: Weigh polyethylene and ethylene-acrylate-maleic anhydride copolymer, and stir to mix evenly; (3) Intermediate layer materials: S1: Mix succinic acid and fumaric acid for later use; S2: Mix 1,4-butanediol and glycerol for later use; S3: adding the mixture of succinic acid and fumaric acid obtained in step S1 and the mixture of 1,4-butanediol and glycerol obtained in step S2 into a reaction container for reaction to obtain the cross-linked unsaturated polyester polyol; S4: mixing dibenzoyl peroxide and ethylene glycol to obtain a chain extender for later use; S5: mixing the cross-linked unsaturated polyester polyol obtained in step S3, the chain extender obtained in step S4, and the catalyst, then adding diisocyanate, adding the mixture to a twin-screw extruder through a feeding and perfusion system, performing reaction extrusion, pelletizing, and drying to obtain a cross-linked thermoplastic polyurethane, which is the intermediate layer material; (4) respectively adding the outer layer material, the middle layer material and the inner layer material into corresponding extruders, and obtaining a three-layer composite film by three-layer co-extrusion blow molding or casting, namely, the substrate film; (5) Applying an adhesive on the inner layer material side of the substrate film to obtain the high temperature resistant swelling tape.

8. The preparation method according to claim 7, characterized in that: In step (4), the temperature of each zone of the outer layer machine corresponding to the outer layer material is 150-180°C, the temperature of each zone of the middle layer machine corresponding to the middle layer material is 140-180°C, the temperature of each zone of the inner layer machine corresponding to the inner layer material is 140-180°C, the temperature of the connecting head of the extruder is 180±10°C, and the temperature of the die head is 170±10°C.

Citation Information

Patent Citations

  • Swelling adhesive tape special for lithium battery and manufacturing process thereof

    CN111518481A

  • High-expansion-ratio oriented polystyrene expansion adhesive tape and preparation method thereof

    CN111995957A

  • Base membrane of swelling adhesive tape for lithium battery and swelling adhesive tape for lithium battery

    CN114213983A

  • Adhesive tape with polyurethane support

    CN114075409A

  • Self-adhesive film for stainless steel and preparation method of self-adhesive film

    CN115157807A